Calculation of Greenland and Antarctica Glaciers' Weights Causing Some Earthquakes and Volcanic Activities - Ürüşan, Ahmet Yücel; Uzel, Turgut; Eren, Kamil (Polish Acad Sciences Inst Physics, Al Lotnikow 32-46, Pl-02-668 Warsaw, Poland, 2014)
Global warming is very important subject for environmental physics. Although the earth seems like inanimate, it acts just like a live mechanism which is called as Glacial-Interglacial Ice. One can consider that there are three periods for this forming, say major (100,000 years), minor (12,000 years) and smaller (1000 years) ice ages. The temperature of the earth is affected by increasing especially CO2 and other sera gases in the atmosphere. The solar radiation reflected from the earth surface cannot go back to the space due to the sera gases and is absorbed by the atmosphere. After the industrial revolution at the beginning of 20th century, especially in the last 30 years, the amount of CO2 and the other carbon gases emitted into the atmosphere has been increasing and causing natural disasters like irregular local temperature changes, floods, melting glaciers, and more powerful hurricanes. The solar radiations are mostly reflected by glaciers which are significant formations on the earth. Melting of these glaciers reduces the surface reflection and causes more absorption of solar radiation by the earth. In addition, sea level, amount of fresh water, and perceptible water vapor in the atmosphere may increase. In this study, Greenland and Antarctica glaciers' weights which press the plates downward are calculated. Melting the glaciers, the plates get rid of the pressure and rise upward over the mantle, and may cause some earthquakes, and volcanic activities such as Thoku earthquake in Japan and Eyjafjallajokull and Grimsvotn volcanos in Iceland.